The Oxford handbook of sound and image in Western art - Kaduri, Yael, 1964- (New York : Oxford University Press, 2016)
"The Oxford Handbook of Sound and Image in Western Art examines, under one umbrella, different kinds of analogies, mutual influences, integrations and collaborations of audio and visual in different art forms. The book represents state-of-the-art case studies with key figures of modern thinking constituting a foundation for discussion. It thus emphasizes avant-garde and experimental tendencies, while analyzing them in historical, theoretical, and critical frameworks. The book is organized around three core thematic sections. The first, Sights and Sounds, concentrates on the interaction between the experience of seeing and the experience of hearing. Examples of painting, classic and digital animation, video art, choreography, and music performance are examined in this section.^
Sitting at the cutting edge of the field of music and visual arts, the book offers a unique, at times controversial view of this rapidly evolving area of study. Artists, curators, students and scholars will find here a panoramic view of cutting-edge discourse in the field, by an international roster of scholars and practitioners."--Publisher's description.
Sound, Space, and Matter explores experimental forms emanating from the expansion of the concepts of music and space to include environmental sounds, vibrating frequencies, silence, language, human habitats, the human body, and more. The reader will find here an analysis of different manifestations of this aesthetic shift in sound art, fine art, contemporary dance, multimedia theatre, and cinema. The last section, Performance, Performativity, and Text, shows how new light shed by modernism and the avant-garde on the performative aspect of music have led it - together with sound, voice, and text - to become active in new ways in postmodern and contemporary art creation. In addition to examples of real-time performing arts such as music theatre, experimental theatre, and dance, it includes case studies that demonstrate performativity in fine art, visual poetry, short film, and cinema.^
Microsound and macrocosm : Gérard Grisey's explorations of musical sound and space / Julia Kursell and Armin Schäfer -- The affective experience of space : Janet Cardiff and George Bures Miller / Mirjam Schaub -- Sound, image, dance, and space in intermedial theatre : past and present / Petra Maria Meyer -- Body soundscape : perception, movement, and audiovisual developments in contemporary dance / Enrico Pitozzi -- Acoustical properties : practicing contested spaces in the films of Philippe Grandrieux / Randolph Jordan -- Silence and void : aesthetics of absence in space and time / Dieter Daniels -- Section III : Performance, performativity, and text. Toward a theory of experimental music theatre : "showing-doing," "non-matrixed performance," and "metaxis" / Björn Heile -- Showing dance : lecture performances in dance since the 1990s / Gabriele Brandstetter -- Object and idea : music in the art of Kandinsky, Duchamp, Paik, and Marclay
boek
Keywords: Audiovisuelle Medien; Installation; Klangkunst; Klangobjekt; Kunst; Medienkunst; Music -- History and criticism